2023
DOI: 10.1002/msc.1760
|View full text |Cite
|
Sign up to set email alerts
|

Work limitations and associated factors in rheumatoid arthritis, axial spondyloarthritis, osteoarthritis and fibromyalgia

Abstract: Introduction: Rheumatic and musculoskeletal diseases (RMD) impact on work participation. The aims of this study were to: examine work limitations of working people with: rheumatoid arthritis, axial spondyloarthritis (axSpA), osteoarthritis, or fibromyalgia using the Workplace Activity Limitations Scale (WALS, a measure of presenteeism); and identify personal, functioning and disability, and work contextual factors associated with presenteeism.Methods: Secondary analysis was conducted of a cross-sectional surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Over a third of the work barriers listed in the WES‐RC were reported as problematic by 25% or more of participants, with the most common being physical problems of prolonged standing, sitting, bending/kneeling/crouching, lifting, and using hands whilst working. Studies investigating work limitations in IA using WALS, similarly identified these as the most common (Brown et al., 2023 ; Gignac et al., 2011 ; Xavier et al., 2019 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Over a third of the work barriers listed in the WES‐RC were reported as problematic by 25% or more of participants, with the most common being physical problems of prolonged standing, sitting, bending/kneeling/crouching, lifting, and using hands whilst working. Studies investigating work limitations in IA using WALS, similarly identified these as the most common (Brown et al., 2023 ; Gignac et al., 2011 ; Xavier et al., 2019 ).…”
Section: Discussionmentioning
confidence: 98%
“…Studies investigating work limitations in IA using WALS, similarly identified these as the most common (Brown et al, 2023;Gignac et al, 2011;Xavier et al, 2019).…”
Section: Updating the Wes-rc Manual And Workwell Solutions Manualmentioning
confidence: 99%
See 1 more Smart Citation
“…Work-related environmental factors associated with presenteeism (i.e., reduced productivity at work) include workplace support, work accommodations (i.e., modifications to a job or work environment to enable an employee with a disability to perform their job duties) and organisational policies and practices (Boonen et al, 2021;Brown et al, 2023;Tang et al, 2011). Assessing such factors, the nature of people's work (full or part-time, self-employed, job demands), and job disruptions experienced, is important to gain a better understanding of people with RMD's ability to work (Heerkens et al, 2017;Tang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing work‐related contextual factors is important to gain a greater understanding of people with RMD’s ability to work (Heerkens et al., 2017; Tang et al., 2011). Amongst work‐related personal factors, those associated with presenteeism (i.e., reduced productivity at work) in RMD include job strain, and work‐life‐health balance (Brown et al., 2023; Gignac et al., 2012). The patient reported outcome measures (PROM) to assess such factors, tested across a range of RMDs, can assist in understanding the biopsychosocial impact of RMDs on work participation as well as help plan and evaluate work interventions.…”
Section: Introductionmentioning
confidence: 99%